New microsatellite markers distinguish two species of ramps (Allium tricoccum Aiton Complex, Amaryllidaceae) and show variation in clonality and genetic diversity between species and among populations - Sarah E. Nilson; Matt C. Estep; Eric P. Burkhart; Harvey Ballard; Ezra Houston; Bina S. Sitepu; Haley Velemirovich; Malia Costa (PLoS ONE, 2025)
A ramp (Allium tricoccum Aiton), or wild leek, is a perennial herbaceous plant native to the forests of eastern North America. Like other members of the Allium genus, ramps produce sulfur-containing compounds that give them culinary and medicinal appeal. Ramps reproduce clonally via bulb division and sexually via seed production, but little is known regarding how much genetic diversity is present in ramps and ramp populations. Furthermore, there is an unresolved question regarding species delineation, with as many as four species suggested. We developed four polymorphic microsatellite markers that we used to measure genetic diversity in ramps and found that ramp populations have low to moderate levels of genetic variation and high differentiation and that individual ramp populations vary in clonality and genetic diversity. Finally, we provide the first preliminary genetic evidence supporting the delineation of the purported second ramp taxon, narrow-leaf ramps (Allium burdickii (Hanes) A.G. Jones).